2009
DOI: 10.1007/s00393-009-0552-1
|View full text |Cite
|
Sign up to set email alerts
|

Sport und Arthrose

Abstract: Many risk factors for developing osteoarthrosis exist. Osteoarthrosis is the most common cause of chronic disability in middle-aged and older people. On the one hand, physical exercise can lead to arthrosis; on the other hand, physical exercise is commonly used in preventing and treating it. Experimental and clinical studies have shown that increased high-impact running or competitive sports result in a higher risk for osteoarthrosis than moderate low-impact running. In particular, sudden-impact loading and tw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 34 publications
0
3
0
2
Order By: Relevance
“…Currently, there are different opinions regarding the effect of running on articular cartilage of the knee. Short interval and regular running seems to have a protective effect on articular cartilage [1][2][3][4]. Similarly, several studies concluded that running a marathon does not increase pathology or osteoarthritis (OA) in the knee joint [5][6][7][8][9][10], and some data indicate a protective effect of long-distance running [11,12].…”
Section: Introductionmentioning
confidence: 99%
“…Currently, there are different opinions regarding the effect of running on articular cartilage of the knee. Short interval and regular running seems to have a protective effect on articular cartilage [1][2][3][4]. Similarly, several studies concluded that running a marathon does not increase pathology or osteoarthritis (OA) in the knee joint [5][6][7][8][9][10], and some data indicate a protective effect of long-distance running [11,12].…”
Section: Introductionmentioning
confidence: 99%
“…The increase in movement due to the dog is an important prophylaxis against cardiovascular diseases [49], which is a frequent reason for hospitalizations [50]. Movement also prevents diabetes, intestinal cancer and age-related falls [51] and even has a positive effect on arthrosis [52].…”
Section: Discussionmentioning
confidence: 99%
“…In addition to this, age is a key factor, and for people over the age of 60 the probability incidence of arthrosis is over 80%. This causes a major economic burden on healthcare systems around the world [ 64 , 72 ].…”
Section: Introductionmentioning
confidence: 99%